Hierarchical NiCo2O4 nanosheets grown on Ni nanofoam as high-performance electrodes for supercapacitors - Gao, Guoxin (2015)
A high-performance electrode for supercapacitors is designed and synthesized by growing electroactive NiCo2O4 nanosheets on conductive Ni nanofoam. Because of the structural advantages, the as-prepared Ni@NiCo2O4 hybrid nanostructure exhibits significantly improved electrochemical performance with high capacitance, excellent rate capability, and good cycling stability.